Budget policy of Ukraine in the crisis period and challenges of the post-war reconstruction of the financial system - Trusova, Natalia; Hrytsenko, O. M.; Трусова, Наталя Вікторівна; Гриценко, О. М. (Запоріжжя : 2024, 2024)
UA: В статті досліджуються трансформація бюджетної політики в кризовому (воєнному) періоді та виклики повоєнної відбудови фінансової системи України. Обґрунтовано, що воєнний стан в Україні призвів до значних кількісних і структурних змін у фінансовій системі держави, зокрема, прискорив зміни в обсязі та в структурі доходів і видатків, пришвидшив зростання обсягу бюджетного дефіциту та стрімкого нарощування державного боргу, а також гальмування розвитку територіальних громад. Скорочення податкових надходжень від деяких видів податків в Україні призвело до зменшення доходів місцевих громад. Доведено доцільність застосування альтернатив та способів залучення фінансової допомоги від міжнародних партнерів та інвесторів у постраждалі від воєнних дій економічно слабкі регіони України, а саме: часткове та тимчасове звільнення інвесторів від податків (наприклад від податку на нерухомість і податку на землю, частково від податку на прибуток). Представлена стратегічна концепція відновлення фінансової системи держави та бюджетних відносин в Україні в кризовий (воєнний) та повоєнний період. EN: The article examines the transformation of budget policy in the crisis (war) period and the challenges of the post-war reconstruction of the financial system of Ukraine. It is substantiated that the budget policy is a direction of the economic policy of the state, aimed "at the optimization and rational transformation of incomes and the use of state financial resources, increasing the efficiency of state investments in the economy, coordination of national and local interests in the field of inter-budgetary relations, regulation of the state debt and ensuring social justice at redistribution of national income It has been proven that the most important component of budget policy is the financial system, which determines long-term economic trends, the effectiveness of the financial mechanism, and the financial security of the state. The war led to significant quantitative and structural changes in the financial system of Ukraine, in particular to changes in the volume and structure of revenues and expenditures, adaptation and simplification of budget legislation, an increase in the volume of the budget deficit, a rapid increase in the state debt, and inhibition of the development of territorial communities. The reduction of tax revenues from some types of taxes in Ukraine led to a decrease in the income of local communities, which even in the pre-war period lacked their own income. Measures for the post-war reconstruction of the countries of Europe and the world are presented. The expediency of using different methods of attracting investors in war-affected and economically weak regions of Ukraine has been proven, namely: partial and temporary exemption of investors investing in production from taxes (for example, from real estate tax and land tax, partially from income tax). The strategic concept of restoring the financial system of the state and budgetary relations in Ukraine in the crisis (war) and post-war period is presented.
Бюджетна політика в кризовий період та виклики повоєнної відбудови фінансової системи України
Keywords: budgetary policy; budgetary relations; financial system; debt burden; budget deficit; fundraising initiatives; international partners; financial assistance; бюджетна політика; бюджетні відносини; фінансова система; боргове навантаження; дефіцит бюджету; фандрейзингові ініціативи; міжнародні партнери; фінансова допомога